A review of factors influencing customer acceptance of internet of things services - Al-Momani A.M.; Mahmoud M.A.; Ahmad M.S. (IGI Global, 2023)
Sales; Web services; Customer acceptance; Different domains; Internet of Things (IOT); IT services; Technology acceptance model; Technology adoption; The unified theory of acceptance and use of technology(UTAUT); User satisfaction; Internet of things